Exploring Caregiver Anxiety in the Daily Care of Systemic Lupus Erythematosus Patients: A Qualitative Study - Wahono, Cesarius Singgih; Pratama, Mirza Zaka; Rahman, Perdana Aditya; Handono, Kusworini (Current Internal Medicine Research and Practice Surabaya Journal, 2026)
Introduction: Caregivers of patients with Systemic Lupus Erythematosus (SLE) face significant emotional and psychological challenges due to the chronic and unpredictable nature of the disease. This study aimed to explore the anxiety experienced by caregivers in their daily caregiving roles. Methods: A qualitative, phenomenological approach was used to gain insights into the lived experiences of 15 caregivers providing daily care to SLE patients. Data were collected through in-depth, semi-structured interviews, and thematic analysis was conducted to identify key themes related to caregiver anxiety. Results: Five main themes emerged: (1) Emotional Burden and Anxiety—Caregivers reported constant worry and stress due to the unpredictability of SLE; (2) Impact on Personal Life and Relationships—Caregiving responsibilities led to feelings of isolation and strained relationships; (3) Coping Mechanisms and Resilience—Caregivers utilized social support, religious practices, and routines to manage their anxiety; (4) Perceived Lack of Professional Support—Caregivers felt overlooked by healthcare providers and expressed a need for more comprehensive support services; (5) Long-Term Outlook and Future Uncertainty—Anxiety about the future and their ability to continue caregiving as they aged was a significant concern. Conclusion: The study highlights the multifaceted nature of caregiver anxiety in the context of SLE. There is a critical need for healthcare systems to provide holistic support that addresses both the emotional and practical needs of caregivers. By enhancing caregiver support, the overall well-being of both caregivers and patients can be improved.